2022
DOI: 10.1007/s00268-022-06630-w
|View full text |Cite
|
Sign up to set email alerts
|

Patient Follow‐up After Orthopaedic Outreach Trips – Do We Know Whether Patients are Improving?

Abstract: Background The burden of traumatic musculoskeletal injuries falls greatest on low- and middle-income countries (LMICs). To help address this burden, organizations host over 6,000 outreach trips annually, 20% of which are orthopaedic. Monitoring post-surgical outcomes is critical to ensuring care quality; however, the implementation of such monitoring is unknown. The purpose of this review is to identify published follow-up practices of short-term orthopaedic surgery outreach trips to LMICs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…Beyond organizational and procedural factors, our study investigated the individual patient factors influencing followups. Previous literature has reported lack of technology and financial costs as major restrictions to patients' ability to be contacted and followed, 8,9 yet to the best of our knowledge, no report has statistically analyzed the correlation between specific SES factors and lack of follow-up. Our study found the majority of SES surrogate factors did not significantly correlate with follow-up attendance, with the exception of phone access.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Beyond organizational and procedural factors, our study investigated the individual patient factors influencing followups. Previous literature has reported lack of technology and financial costs as major restrictions to patients' ability to be contacted and followed, 8,9 yet to the best of our knowledge, no report has statistically analyzed the correlation between specific SES factors and lack of follow-up. Our study found the majority of SES surrogate factors did not significantly correlate with follow-up attendance, with the exception of phone access.…”
Section: Discussionmentioning
confidence: 97%
“…6 Commonly noted barriers to follow-up care include weak or overwhelmed local infrastructure and logistical issues at the mission sites, including language constraints. 7,8 Sykes reported that some medical service organizations may not prioritize standardized evaluation tools, data collection, and analysis because research is thought to provide only limited mission benefits. 6 Other NGO's presume lack of technology, financial costs, misunderstandings about the need for further care, or remote location of a patient's home as barriers for patients' follow-up care and data collection.…”
Section: Introductionmentioning
confidence: 99%
“…Over 500 outreach organizations exist in the USA and an estimated 6000 trips are conducted annually [7,8], typically aiming to increase access to much needed surgical services. However, the lasting impact of such trips has been criticized due to their short-term nature, perpetuation of voluntourism and colonialist practices, limited preparation and training in local care and customs, sparse outcome collection, and lack of regulation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of such partnerships, however, is not always known. For example, 2 recent systematic reviews have questioned the long-term impact of short-term outreach trips in orthopaedic surgery and plastic and reconstructive surgery, with both studies citing concerns related to low levels of follow-up, accountability, and complication rates 6,7 .…”
mentioning
confidence: 99%